Effectiveness of warm herbal compress on oxytocin hormone and breast milk production - Laksonowati, Setyo Mahanani; Runjati, Runjati; Ta’adi, Ta’adi; Mulyantoro, Donny Kristanto; Kholifah, Kholifah (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2021)
Background: Breast milk is the best food for babies, needed for optimal growth and development. The lack of milk production influences the low coverage of exclusive breastfeeding. Increasing breast milk production could be done non-pharmacologically, using warm herbal compresses as breast care. Purpose: Analyze the effect of warm herbal compresses as breast care on oxytocin hormone and postpartum mother’s milk production. Methods: Quasi-experimental design pretest-posttest with the control group, respondents were 36 normal mothers on the third day of postpartum; 18 respondents intervention group, and 18 respondents control group. Warm herbal compresses were provided once per day with 20 minutes on each breast for three days. The oxytocin hormone was measured pre and post three days of treatment, the volume of breast milk was measured pre, post 2, and 3 days of treatment. Results: The intervention group’s average difference in oxytocin hormone was 24.65 pg/ml, the control group was 2.48 pg/ml (p<0.01). The average increase in milk production pre and post-three days of treatment in the intervention group was 32,250 ml. In the control group, 26,472 ml (p<0.01), there was a significant difference in the average milk production between the two groups. Conclusion: Warm herbal compresses as breast care affects the oxytocin hormone and postpartum mother’s milk production.